2015
DOI: 10.1089/ten.tec.2015.0129
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of α-Gal Antigen Removal in the Porcine Dermal Tissue by α-Galactosidase

Abstract: The α-Gal (Galα1,3-Galβ1-4GlcNAc-R) epitope, the major xenoantigen, is the first barrier in a porcine-to-man tissue and organ xenotransplantation. The elimination or reduction of the α-Gal epitopes is therefore an important step for a successful xenotransplantation. The present study is to evaluate the α-Gal elimination in the porcine skin with α-galactosidase treatment, and to assess two methods (immunohistochemistry and inhibition ELISA) that may be used in quality control for quantifying the extent of the α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It also plays a pivotal role in tissue morphogenesis and organ development, thus providing the most suitable environment for the cells [7][8][9]. Through physical, chemical and biochemical methods, dECM is prepared by preserving the basic structural and functional ECM proteins of tissue and removing the cellular components that might cause immune rejection or inflammatory responses [10][11][12]. Although various studies have been focused on 3D constructs based on the use of dECM, there is a general lack of research on changes in gene expression within the 3D construct.…”
Section: Introductionmentioning
confidence: 99%
“…It also plays a pivotal role in tissue morphogenesis and organ development, thus providing the most suitable environment for the cells [7][8][9]. Through physical, chemical and biochemical methods, dECM is prepared by preserving the basic structural and functional ECM proteins of tissue and removing the cellular components that might cause immune rejection or inflammatory responses [10][11][12]. Although various studies have been focused on 3D constructs based on the use of dECM, there is a general lack of research on changes in gene expression within the 3D construct.…”
Section: Introductionmentioning
confidence: 99%
“…Study has shown that treatment of an enzyme a-galactosidase on xenogeneic scaffolds could eliminate a-Gal epitopes from the animal tissue. 12 According to a recent report, when decellularized porcine a-Gal knockout lungs and decellularized lung containing a-Gal epitope were recellularized with human lung cells, there was no difference found in terms of cell growth and proliferation in both the lung recellularization. 13 Commercial glutaraldehydefixed heart valve transplantation exhibits anti-gal antibody immune reactions in humans and non-human primates.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of enzyme digestion is that it can be used to digest and destroy cell membranes. The enzyme α‐Gal glycosidase acts in a specific manner against the α‐Gal antigen and has been applied extensively to remove the α‐Gal antigen in porcine skin and heart valves . Trypsin is a non‐specific enzyme, which is used as a decellularization agent in cell harvesting protocols.…”
Section: Discussionmentioning
confidence: 99%